The association between WHO grading and the long-term outcomes and radiotherapy efficacy of intracranial solitary fibrous tumors - Leihao Ren; Lingyang Hua; AO Feng; Jiaojiao Deng; Hiroaki Wakimoto; Tareq Juratli; Qing Xie; Ye Gong (Acta Neuropathologica Communications)
Abstract Background Intracranial solitary fibrous tumor (SFT) is a rare mesenchymal tumor of fibroblastic origin in the central nervous system (CNS). The 2021 WHO classification of CNS tumor has updated the entity and grading criterion of SFT. We aimed to compare the 2021 WHO grading criterion (2021-WGC) and 2016 WHO grading criterion (2016-WGC) for their value to predict prognosis and radiotherapy (RT) efficacy. Methods This is a retrospective study involving 223 consecutive intracranial SFT patients who received tumor resection at our neurosurgical center from 2013 to 2021. Univariable and multivariable Cox regression analyses were utilized to identify prognosis-related factors and evaluate the efficacy of RT. A risk model was constructed to predict the long-term recurrence. Results A total of 223 SFT patients were included in this study. During a median follow-up period of 4.67 years, 80 (35.9%) patients experienced tumor recurrence and 14 (6.3%) experienced extracranial metastasis. Patients with SFT who developed recurrence were significantly older at diagnosis and exhibited higher Ki-67 index and mitotic count. Of note, the PFS of 2016-WGC grade 3 tumors was worse than the comparable PFS of grade 1 and 2 tumors (P = 0.001), while the PFS of 2021-WGC grade 1 tumors was better than grade 2 and 3 tumors that showed similar PFS in the long term (P < 0.001). We further proposed a novel risk stratification method that demonstrated a superior prognostic value compared to the 2021-WGC and 2016-WGC. Additionally, RT significantly prolonged the PFS of SFT patients, especially beyond 3 years after surgery (P = 0.032). Further efficacy analysis showed that RT prolonged PFS in the 2016-grade 3 tumors. While with the 2021-WGC and novel risk stratification, RT prolonged PFS in the 2021-grade 2 and intermediate risk tumors, respectively. Conclusions The 2016-WGC identified high-recurrence risk patients in grade 3 while the 2021-WGC identified low-recurrence risk patients in grade 1. RT significantly prolonged PFS in SFT patients, especially after 3 years post-surgery. Notably, RT significantly improved PFS in the 2016-grade 3, 2021-grade 2 and intermediate risk tumors.